From Kitchen To Agriculture – Transforming The Wealth of Natural in Egg Shells Into Organic Fertilizer - Anatasia, Velly; Iskandar, Viriya Fuzzel; Tukan, Vinsensia E. Ose (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
Eggshells are a common type of kitchen waste that are often left unused, despite their high calcium content. Calcium plays a vital role in supporting plant growth, particularly in the agricultural sector. Based on this potential, the present study aims to investigate the use of eggshells as the primary ingredient in the production of nutrient-rich, organic fertilizer. Organic fertilizer made from eggshells provides an environmentally friendly alternative to meet the nutritional needs of food crops, particularly amid the growing demand for organic fertilizers. This research adopts a qualitative approach, with data collected through interviews with MSME (Micro, Small, and Medium Enterprises) plant sellers in Jakarta to understand their needs and the potential for using organic fertilizers. The production process involves relatively simple steps but requires a lengthy fermentation period. The findings indicate that eggshells can be transformed into effective organic fertilizer with high practical value for the agricultural sector. This study is expected to provide an innovative solution to address the demand for organic fertilizers while simultaneously reducing unprocessed household waste, thereby contributing to the reduction of domestic waste in Indonesia.